Alan Dundes, Carl R. Pagter: When You´re Up to Your Ass in Alligators. More Urban Folklore from the Paperwork Empire.: Wayne State University Press, Detroit 1987 - Janeček, Petr (Lidé města, 2005)
A review of the book by Alan Dundes and Carl R. Pagter.